Automatic assignment of 1H‐NMR spectra of small molecules. (23rd August 2013) - Cobas, C.; Seoane, F.; Vaz, E.; Bernstein, M. A.; Dominguez, S.; Pérez, M.; Sýkora, S.
Abstract A novel data‐evaluation procedure for the automatic atom to peak or multiplet assignment of 1H‐NMR spectra of small molecules has been developed using a fast and robust expert system. The applicability and reliability of the method are demonstrated by comparison of a manually assigned database of 1H‐NMR spectra with the assignments produced by the automatic procedure. The results of this analysis show an excellent success ratio, indicating that this new algorithm can have a major impact as a time saving tool for the organic chemist. A new graphical feature used to illustrate both the stability and quality of the elementary assignments is also introduced. Copyright © 2013 John Wiley & Sons, Ltd.